B.I.B.L.I.O. Master: learning platform for mastering APA 7th Edition citation styles - Mohd Fazil Jamaludin, Mohd Fazil; Saharan, Mohd Shafiz; Adzahar, Khairul Azfar; Muhamad, Marlina; Hassam, Siti Fairuza (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This groundbreaking gamified platform is focused on developing a more motivating, engaging, and interactive learning environment where students can learn the APA 7th Edition citation styles. Thanks to the vivid and real-life interactivity, the platform increases students' sense of presence, their social interaction, promotes students' knowledge acquisition, and leads to improved material comprehension. B.I.B.L.I.O. Master creates secure, safe, immersive, and interactive learning spaces that prioritize the student. The platform promotes active participation, offers a sense of presence, enables individual and collaborative learning, and allows engagement in activities which would be impossible in usual conditions. Students that are using such gamified environments shown better performance, higher motivation and engagement, better psychological states and behavior, and retention of knowledge. The platform increases the level of focus on students, whereas it also fosters imagination and curiosity, thus the understanding of the subject matter in a more interesting, fun, and engaging way rather than with traditional learning. The platform provides specific, simple instructions and aims, guided activities that stimulate student intrinsic and extrinsic motivations, real-time and personalized feedback, and allows students to learn at their own pace, reflect upon their results, and control the activities themselves. Using student-centered approaches in the design and creation of such experiences guarantees maximum effectiveness. The results of the implementation have indicated that B.I.B.L.I.O. Master is a source of innovation in teaching and learning. The majority of the studies confirmed a positive effect on the learning process and students' satisfaction. It brings to the educational process by being an effective tool for educator and meeting students' demands for more productive learning effectively.